PERSON-CENTERED INTERVIEW AS A TOOL FOR CLINICAL WORK IN MYOCARDIAL INFARCTION SETTING - E. O. Taratukhin; M. A. Kudinova; О. Yu. Shaydyuk; A. L. Golovkina; S. N. Vaslyaeva (Кардиоваскулярная терапия и профилактика)
The issue of non-communcable diseases risk factors is one of the main in global targets of healthcare.  However the key point in this direction is still a  patient-clinician  communication  that  demands   high  level  of understanding and  empathy.  A  useful tool for clinical work might be person-centered interview.Aim. To evaluate epistemological role of person-centered interview and to define its place in cardiological care for acute  myocardial infarction patients (MI).Material and methods. The study is done in qualitative methodology: in-depth semistructured interview. Totally, 216 consequent MI patients screened. After inclusion  criteria  assessment  (economically  active males  with first MI, none  severe  comorbidities  and  no anamnesis  of coronary heart disease)  and study procedures, 14 interviews included into analysis  by phenomenological  descriptive  with the  elements  of interpretation, method.Results. A range of non-expressed experiences  revealed of the living through of the disease state in this group of patients: serious life change, borderline of life “before” and “after”; anxiety and fear of sudden death and repeat  of the event; discourage  and confusion; puzzlement; disorientation in symptoms,  misunderstanding;  loss of perspective  for better  in life; stigmatization; self-image  changes; feelings of guilt and resentment;  somatic markers; specifics of social stress.Conclusion.  Person-centered  interview as  a  method  of  dialogue, implemented  to  the  work of clinician, makes  it to  reveal  the  nonexpressed  but  very important  sides  of  the  disease   course.   In the experiencing of males with first MI, economically active, there is a range of issues  requiring specific  work. Addressing  to the  phenomenal  of patients  might be  a  higher  level position  in the  work with life style determined non-communicable diseases.